2021
DOI: 10.1007/s00203-021-02295-6
|View full text |Cite
|
Sign up to set email alerts
|

Noviherbaspirillum pedocola sp. nov., isolated from oil-contaminated experimental soil

Abstract: An orange-coloured, rod-shaped, and aerobic bacterial strain DKR-6 T was isolated from oil-contaminated experimental soil. The strain was Gram-stain-negative, catalase and oxidase positive, and grew at temperature 10-42 °C, at pH 5.5-9.5, and at 0-3.0% (w/v) NaCl concentration. The phylogenetic analysis and 16S rRNA gene sequence analysis suggested that the strain DKR-6 T was affiliated to the genus Noviherbaspirillum, with the closest species being Noviherbaspirillum massiliense JC206 T (96.3% sequence simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Furthermore, we indicated that bacteria so far not recognized as degraders may also participate in alkane conversion; namely the Noviherbaspirillum and Flavihumibacter taxa. Although there are no reports of alkane transformation by these bacteria, the representative of the former genus was previously isolated from oil-contaminated soil (Chaudhary et al 2021 ). Searching for alkB genes in the genomes belonging to these genera revealed the presence of 4 and 3 mentioned genes in respectively 14 genomes of Noviherbaspirillum and 11 genomes of Flavihumibacter (NCBI GenBank data from 31 May 2023, the result of sequence homology analysis performed using Blast).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we indicated that bacteria so far not recognized as degraders may also participate in alkane conversion; namely the Noviherbaspirillum and Flavihumibacter taxa. Although there are no reports of alkane transformation by these bacteria, the representative of the former genus was previously isolated from oil-contaminated soil (Chaudhary et al 2021 ). Searching for alkB genes in the genomes belonging to these genera revealed the presence of 4 and 3 mentioned genes in respectively 14 genomes of Noviherbaspirillum and 11 genomes of Flavihumibacter (NCBI GenBank data from 31 May 2023, the result of sequence homology analysis performed using Blast).…”
Section: Discussionmentioning
confidence: 99%
“…Strain DKR-3 T was recovered from laboratory-prepared experimental oil-contaminated soil during a study of bioremediation and subjected to a polyphasic study for determination of its taxonomic position. The isolation, maintenance and preservation of strain DKR-3 T were performed following the methodology described in a previous study [10].…”
Section: Isolation and Ecologymentioning
confidence: 99%
“…Cells of this genus are Gram-stain-negative and non-spore-forming. The predominant quinone is Q-8, with major fatty acids being summed feature 3 (C 16 : 1 ω6c/C 16 : 1 ω7c), summed feature 8 (C 18 : 1 ω7c/C 18 : 1 ω6c), and straight-chain saturated fatty acids [1][2][3][4][5][6][7][8][9]. The polar lipid profile includes diphosphatidylglycerol (DPG), phosphatidylglycerol (PG), phosphatidylethanolamine (PE), and phosphatidylcholine (PC) [1].…”
mentioning
confidence: 99%
“…Flagellar-related proteins, including chemotaxis proteins, transcriptional activators, motor switch proteins, and biosynthesis proteins, were found in all analysed genomes (Table S3). This suggested that flagellar motility is common in the genus Noviherbaspirillum, although N. pedocola DKR-6 T has been reported to lack flagella [2]. *Summed features are fatty acids that cannot be resolved reliably from another fatty acid using the chromatographic conditions chosen.…”
mentioning
confidence: 99%
See 1 more Smart Citation